Pengukuran Kesehatan Bank Syariah Berdasarkan Islamicity Performance Index - Muhammad Makruflis (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2019)
This research is motivated by the performance of Islamic banks in Pekanbaru as measured in terms of the Islamicity Performance Index. This research is field research, with qualitative descriptive methods. The sampling method uses simple random sampling. The number of respondents in this study amounted to 93 people. Data collection is done by means of observation, interviews, documentation and questionnaires. Based on strategic planning and Islamicity Performance Index using Islamic economic perspective in the form of financial ratios namely profit sharing ratio, zakat performance ratio, equitable distribution ratio, director employee welfare ratio, Islamic investment versus non-Islamic investment ratio and Islamic income versus non-Islamic income and more focused the zakat performance ratio shows that the financial performance of Bank Muamalat Indonesia is better than Bank Syariah Mandiri.